A COMPREHENSIVE SURVEY ON MULTIPLE ATTACKS IN NAMED DATA NETWORK - A. Abdul Faiz; Sheelaselvakumari, N. A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Named data network is a future architecture of internet, which acts as a data-centric model. The NDN designed as an alternative to the current IP (Internet Protocol) based architecture, which relies on addressing devices and routing packets between them. NDN, on the other hand, focuses on naming data rather than devices in the network. As like its popularity nature, NDN suffers from different types of security vulnerabilities such as are cache pollution attacks (PA), cache poisoning attack (CPA), interest flooding attack (IFA) and Distributed denial of service (DDOS) attacks, which affects the data integrity, privacy, availability and confidentiality. These attacks made impacts on developing a security framework for NDN. This paper provides a review of existing solutions against the NDN vulnerabilities in detailed manner. This finally provides the complication and drawbacks of those existing solutions and thus helps to navigate to a future mechanism generation.